PEMBERDAYAAN PETANI MELALUI PENGOLAHAN LIMBAH JERAMI PADI MENJADI PUPUK BOKASHI UNTUK TANAMAN PADI (Oryza sativa L.) - Dea Marini; Muhammad Tassim Billah; Yul Harry Bahar (Jurnal Inovasi Penelitian, 2020)
Indonesia is an agricultural country with a majority in rice farming. Every year there is an increase in rice production resulting in an increase in the amount of agricultural waste such as straw. The habits of farmers in Cimalaka Subdistrict, which are burning straw to reduce agricultural waste, have a negative impact on the environment. The content of the elements in straw can be reused for rice plants and can increase soil fertility, therefore a study was carried out under the heading " Farmer Empowerment through Processing Rice Straw Waste into Bokashi Fertilizer for Rice Plants (Oryza sativa L.) in Cimalaka District". The purpose of this study is to describe the level of empowerment of farmers in processing rice straw waste into bokashi fertilizer, analyzing the factors related to empowering farmers through processing rice straw waste into bokashi fertilizer and identifying extension strategies to improve farmer empowerment. The assessment was carried out for 4 months (March-June) in Cimalaka District. The sampling technique was done by purposive sampling totaling 52 respondents. The type of data consists of secondary data and primary data. Data obtained through direct interviews and questionnaires that have been tested for validity and reliability. Data were analyzed descriptively and partial correlation. The results showed that the empowerment of farmers in processing straw into bokashi fertilizer in Cimalaka District was quite high. Factors associated with empowering farmers through processing rice straw waste into bokashi fertilizer are the level of education, the role of extension workers and sources of information. The strategy that can be done to improve farmer empowerment is through counseling through demonstration of how to make bokashi fertilizer to improve farmers' skills.